The Role of Audit Committees in Gauteng Local Government - Venkile, Khanya (University of the Witwatersrand, Johannesburg, 2025)
This study explores the roles of audit committees within local government in Gauteng, South Africa, with a particular focus on their oversight of non-financial performance metrics and the promotion of ethical governance. Through a qualitative research approach that encompasses document analysis and semi-structured interviews with key stakeholders, including audit committee members, senior managers of municipalities, and representatives from the Auditor- General of South Africa, the study seeks to understand stakeholder perceptions of audit committee roles and the integration of non-financial metrics into governance practices. Findings reveal that while audit committees are recognised as essential for ensuring financial integrity, their focus tends to be predominantly on financial reporting, often neglecting broader non-financial performance indicators that reflect community impact and service delivery effectiveness. Additionally, inconsistencies in audit charters across municipalities, a lack of standardised guidelines, and significant challenges, such as limited access to information, inadequate training, and political pressures, impede audit committees from fulfilling their oversight responsibilities effectively. The research highlights the necessity for audit committees to redefine their roles, extending their focus to include comprehensive governance practices that integrate non-financial performance metrics and reinforce ethical standards. Ultimately, the study contributes to the ongoing discourse on local government governance by providing practical recommendations to enhance the functionality and relevance of audit committees, thereby improving accountability and transparency within municipal operations.
A research report submitted in fulfillment of the requirements for the Master of Management in Governance and Management, in the Faculty of Commerce Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; AUDIT COMMITTEES; LOCAL GOVERNMENT; NON-FINANCIAL PERFORMANCE; TRANSPARENCY; SDG-16: Peace, justice and strong institutions; SDG-11: Sustainable cities and communities